COMPARATIVE CHARACTERISTICS OF TTA OF THE WORLD'S LEADING FOOTBALL CLUBS - Andrii Pertsukhov; Borys Beziazychnyi; Viktoria Khudiakova (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to determine model indicators of performing technical and tactical actions by high-level teams. Material and methods: registration of technical and tactical actions was carried out on the example of games of participating teams in the 2020/2021 UEFA Champions League. A total of 242138 technical and tactical actions in 25 games of the teams «Manchester City» (Manchester, England), «Chelsea» (London, England), «Olympique» (Marseille, France), «Olympiacos» (Piraeus, Greece), «Porto» (Porto, Portugal), «Krasnodar» (Krasnodar, Russia), «Rennes» (Rennes, France), «Sevilla» (Sevilla, Spain), «Atletico» (Madrid, Spain), «Borussia» (Dortmund, Germany), «Borussia» (Monchengladbach, Germany), «Real» (Madrid, Spain), «Paris Saint-Germain» (Paris, France) were registered and analyzed. The following research methods were used to solve the tasks: analysis of scientific and methodological literature, registration of technical and tactical actions, methods of mathematical statistics. Results: the article presents data characterizing features of the defensive and attacking TTA by high level teams based on the results of the 2020/2021 UEFA Champions League games. Model indicators of making the ball passes (different in purpose, distance, direction, trajectory, method of performance), shots on target (with a foot and head from different areas of the football field), dribbling of an opponent, aerial duels, tackles, interceptions, knocking out the ball, blocking strikes into the goal have been developed. Conclusions: the data of the study show differences in the structure of competitive activity of different level teams in the games of the 2020/2021 UEFA Champions League. The winning team outnumbered their rivals in almost every indicator.